Pemberdayaan UMKM pada Era Digital Wilayah Perbatasan di Desa Suka Maju Kabupaten Bengkayang - Hutajulu, Teguh; Fahruna, Yulyanti; Monika, Sherlly Santa; Tiabela, Tiabela; Velisia, Velisia; Sitohang, Natalia Putri (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
The purpose of empowering MSMEs is to increase awareness of digitalization and find out how Ruspendi MSMEs are adapting to the increasingly growing era of digitalization. This article focuses on efforts to empower Micro, Small and Medium Enterprises (MSMEs) through digitalization in the business environment. This research was conducted in Semidang Hamlet, Suka Maju Village, Sungai Betung District, Bengkayang Regency. This article uses a qualitative research approach with a case study method for Ruspendi MSMEs. Based on the results of the discussions that have been carried out, it shows that Ruspendi MSMEs are starting to realize the importance of digitalization. Apart from that, it was found that several digitalization strategies had been implemented by Ruspendi MSMEs, such as using Facebook as a marketing medium and using Google Maps to increase operational efficiency.